Optical diagnosis of a kHz-driven helium atmospheric pressure plasma jet. (27th June 2022) - McDonnell, C.; Irwin, R.; White, S.; Graham, W.G.; Riley, D.
Abstract : This paper focuses on utilizing several different optical diagnostics to experimentally characterize a pure helium atmospheric pressure plasma jet. Axial electric field measurements were carried out along the plasma plume through the use of a non-perturbing method based on polarization-dependent Stark spectroscopy of the helium 492.2 nm line. The electric field is shown to increase with distance along the plume length, reaching values as high as 24.5 kV cm^-1 . The rate of increase of the electric field is dependent on the helium gas flow rate, with lower gas flows rising quicker with distance in comparison with larger flow rates, with the typical values remaining within the same range. This sensitivity is linked to gas mixing between the helium and surrounding ambient air. Schlieren imaging of the gas flow is included to support this. The addition of a target is shown to further increase the measured electric field in close range to the target, with the magnitude of this increase being strongly dependent on the distance between the tube exit and target. The relative increase in the electric field is shown to be on average greater for a conducting target of water in comparison with plastic. A minimal equipment optical configuration, which is here referred to as fast two-dimensional monochromatic imaging, is introduced as an approach for estimating excited state densities within the plasma. Densities of the upper helium states for transitions, 1s3s ^3S_1 → 1s2p ^3P^0_0, 1, 2 at 706.5 nm and 1s3s ^1S_0 → 1s2p ^1P^0_1 at 728.1 nm, were estimated using this approach and found to be of the order of 10^10 –10^11 cm^-3 .